Enhanced functional synchronization of medial and lateral PFC underlies internally-guided action planning - Rosenberg Katz, Keren; Jamshy, Shahar; Singer, Neomi; Podlipsky, Ilana; Kipervasser, Svetlana; Andelman, Fani; Neufeld, Miri; Intrator, Nathan; Fried, Itzhak; Hendler, Talma (Frontiers in Human Neuroscience, 2012)
Actions are often internally guided, reflecting our covert will and intentions. The dorsomedial prefrontal cortex, including the pre-Supplementary Motor Area (pre-SMA), has been implicated in the internally generated aspects of action planning, such as choice and intention. Yet, the mechanism by which this area interacts with other cognitive brain regions such as the dorsolateral prefrontal cortex, a central node in decision making, is still unclear. To shed light on this mechanism, brain activity was measured via fMRI and intracranial EEG in two studies during the performance of visually cued repeated finger tapping in which the choice of finger was guided by either a presented number (external) or self choice (internal). A functional-MRI study in 15 healthy participants demonstrated that the pre-SMA, compared to the SMA proper, was more active and also more functionally-correlated with the dorsolateral prefrontal cortex during internally- compared to externally- guided action planning (p<0.05, random effect). In a similar manner, an intracranial-EEG study in 5 epilepsy patients showed greater inter-regional gamma related connectivity between electrodes situated in medial and lateral aspects of the prefrontal cortex for internally- compared to externally-guided actions. Although this finding was observed for groups of electrodes situated both in the pre-SMA and SMA-proper, increased intra-cluster gamma related connectivity was only observed for the pre-SMA (sign-test, p<0.0001). Overall our findings provide multi-scale indications for the involvement of the dorsomedial prefrontal cortex, and especially the pre-SMA, in generating internally-guided motor planning. Our intracranial-EEG results further point to enhanced functional connectivity between decision making- and motor planning aspects of the PFC, as a possible neural mechanism for internally generated action planning.